(untitled) (Simbiótica. Revista Eletrônica, 2026)
Over the past decade and a half, various local initiatives and policies on international migration have been developed in South America. This article analyzes these policies, from the perspective of critical migration and border studies, and examines their role in reconfiguring regional migration governance. Through documentary analysis and the mapping of local initiatives (based on the triangulation of secondary sources), we identify three main types of interventions: the international organization programs (Solidary/Inclusive Cities, MigraCities); municipal networks (Mercociudades); and border mechanisms (Border Integration Committees and Zones). We group these experiences into direct initiatives, focused on local policies aligned with global standards, and indirect initiatives, which incorporate migration into broader agendas, reproducing technocratic logics. The findings reveal a multiscalar articulation (local–national–global) in which devices that define the legitimate ways of “being a migrant” stand out. The “good practices” promoted by international organizations emerge as a structuring axis, albeit with fragmented implementations and uneven outcomes.